Mathematical Model of an Open Area of Space Sensor - A. A. Jezhora; Y. A. Zavatski; A. V. Kovalenko; A. M. Naumenko (Приборы и методы измерений)
For the effective use of dielectric sensors, optimization of the design parameters of the sensors, such as the depth of penetration of the electromagnetic fi and the magnitude of the sensor signal, is of great importance. The purpose of the work was to build a mathematical model of a sensor with an open area of space and calculate its parameters.Results of main parameters calculations of the open space sensor are presented. Methods of integral equations and mirror images are used for numerical 2D modeling. The surface of each electrode was considered as two parallel lamellae. This approach simplifi the procedure for numerically solving a two-dimensional problem. It allows you to calculate the electric fi of fl layered media with less time, using less powerful computers. The numerical calculation program is implemented in MAPLE.The program adequacy was checked for a sensor made on one-sided foil Tefl (ε1 = 2,3) with a thickness of b = 1.0 mm. The electric fi was calculated for the sensor in a three-layer medium. The calculated picture of the fi showed that the distribution of force lines is not uniform. It was found that the depth of the control zone does not depend on the metallization of the sensor surface. The depth of the control zone for an open-type sensor is in the same range as the depth of the control zone for fl overhead measuring capacitorsan analog of fringing electric fi d (FEF) sensors.